First‐Line Osimertinib for EGFR‐Mutated Squamous Cell Lung Carcinoma: A Case Report - Yugo Matsumura; Seiya Ichihara; Kaori Nii; Kazumasa Nanjo; Naoki Kadota; Yoshio Okano; Hisanori Machida; Nobuo Hatakeyama; Hiroyuki Hino; Keishi Naruse; Tsutomu Shinohara; Shoji Sakiyama; et al. (Cancer Reports)
ABSTRACT Background Epidermal growth factor receptor (EGFR) mutations in squamous cell lung carcinoma are rare. EGFR‐tyrosine kinase inhibitors are generally less effective for EGFR‐mutated squamous cell lung carcinoma. We herein present a case of EGFR‐mutated squamous cell lung carcinoma that responded to osimertinib. Case A 75‐year‐old woman with bloody sputum and left back pain was referred to NHO Kochi Hospital. A mass was observed in the left lower lobe on chest CT. Squamous cell lung carcinoma, cT4N1M1b (adrenal metastasis) stage IVA, was diagnosed based on the findings of a CT‐guided percutaneous lung biopsy and a CT scan revealing right adrenal metastasis. The primary tumor was subjected to a genomic analysis with the AmoyDx Pan Lung Cancer PCR panel, which revealed an EGFR mutation (exon 21 L858R). The PD‐L1 tumor proportion score was 95%. Osimertinib was initiated as first‐line targeted therapy. Tumor shrinkage was observed and maintained over 9 months of treatment. Conclusion We encountered a rare EGFR‐mutated squamous cell lung carcinoma that responded well to osimertinib. Osimertinib may be an option for the treatment of patients with EGFR‐mutated squamous cell lung carcinoma.